Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00011-012-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammatory response in human chondrocytes by lentiviral mediated RNA interference against S100A10

Abstract: Our investigation demonstrated that S100A10 might be considered as a potential target for anti-inflammatory treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…As for S100 proteins, PRRSV infection promoted secretion of S100A10. Previous studies have demonstrated that knockdown of S100A10 inhibits the secretion of inflammatory cytokines and S100A10 could interact with annexin A2 (AnxA2), which was implicated in the process of virus entry and replication . Our data show that AnxA2 was also upregulated in response to PRRSV, indicating that S100A10 and AnxA2 may be involved in the inflammatory response and/or replication process of PRRSV.…”
Section: Discussionsupporting
confidence: 58%
“…As for S100 proteins, PRRSV infection promoted secretion of S100A10. Previous studies have demonstrated that knockdown of S100A10 inhibits the secretion of inflammatory cytokines and S100A10 could interact with annexin A2 (AnxA2), which was implicated in the process of virus entry and replication . Our data show that AnxA2 was also upregulated in response to PRRSV, indicating that S100A10 and AnxA2 may be involved in the inflammatory response and/or replication process of PRRSV.…”
Section: Discussionsupporting
confidence: 58%
“…The upregulated transcripts comprise chemokine (C-X-C motif) ligand 13, CXCL13 (FC 79.22), CXCL9/MIG (FC 11.16), chemokine (C-C motif) ligand 18, CCL18 (FC 20.32), interleukin 1 receptor, type I, IL1R1 [30,31] (FC 5.67), oxidized low density lipoprotein receptor 1, OLR1/LOX1 (FC 83.1), S100 calcium binding protein namely S100B [32] (FC 7.8) and S100A102 [33] (FC 2.21), fibronectin1, FN1 [34] (FC 405.4), tumour necrosis factor alpha TNF (FC 3.5).…”
Section: Resultsmentioning
confidence: 99%
“…49 Recent studies reported on special functions of S100 subtypes in chondrocytes. S100A10 seems to play a role in inflammatory responses in human chondrocytes, 50 whereas S100A12 seems to be involved in the pathogenesis of osteoarthritis by upregulating matrix metalloproteinase 13 (MMP13) and vascular endothelial growth factor (VEGF) both associated with the progression of osteoarthritis. 51 These observations are in line with the statement of Donato et al that particular S100 proteins could be induced in pathological circumstances in a cell type that does not express it in normal physiological conditions.…”
Section: Discussionmentioning
confidence: 99%